IMPLEMENTASI KEBIJAKAN OPTIMALISASI PEMANFAATAN PEKARANGAN MODEL KAWASAN RUMAH PANGAN LESTARI - Hidayat, Asep (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
The policy of Accelerating Food Consumption Diversification (P2KP) is basically to reduce the dependence on rice this is due to the switch function of rice fields that changed the function of building in the form of housing and factory and replace the rice as carbohydrates with potatoes, sweet potato, purple yam, taro, breadfruit , maize. banana beside that also with replacement of staple food source with other type is expected to improve the quality of nutrition, and also optimize of yard area through model of home gardening (KRPL) to guarantee the availability of fresh vegetables for self consumption or sold by group, from KRPL This shows the benefits received by citizens who can save household expenses, so as to produce reduced family burden of about Rp. 150.000, - to 250.000, - / month. Program optimization of yard utilization can increase community participation to participate in agriculture development in particular, and involvement of woman role joined in Group can give opinion starting from planning stage until implementation, can innovate with technology of agriculture field.